A competência municipal para legislar sobre contratações públicas sustentáveis - Desordi, Danubia (2019)
In view of the sustainable national development promotion inclusion among the goals to be pursued by public hires, arises the research problem, which is identify the municipality limitation to editing rules about sustainable public hires, considering the legislative competence conferred to federate entities by Federal Constitution. The general goal is to analyze the municipality competence to legislate about sustainable public hires. The specifics objectives to be pursue are evaluate the sustainable fundament and sustainable development, considering your environmental dimensions, social and economic, and your influence on Brazilian legal system and state formation; understand municipality position and competences on the Brazilian federation state, notably the legislative prerogative, gives to each federate entity, for rules edition about bids and administrative contracts; and, evaluate the models of sustainable public contracts regulations, edited by Brazilian capitals, objecting to identify the observance with constitutional limits established to exercise your competence, as well as sustainable criteria concretization on municipality public acquisitions. To the dissertation development, was used as approach method, the hypothetical-deductive, and as procedural method, the monographic. The technique to be used is basic bibliographic, with support on national regulatory instruments, and bibliographic sources, as books, publications and periodicals. Jurisprudence and bidding notices were also used. From the study, was possible to conclude that municipality has competence to regulation of sustainable public hires, through the specific rule edition, respecting the general guidelines established by Union on national standards. Plus, could be glimpsed that, although few federal capitals had instructed regulations about the topic, the sustainable criteria implementation, on municipals public acquisition, shows highly relevant, considering the amount of resources spent and the possibility of your utilization as instrument to public policies promotion that encourage the sustainable development locally.